Investigation of Deviations Between Measured and Calculated Peaking Factors at Ringhals 3 - Mybeck, Markus (My University, 2015)
The startup of cycle 32 for Ringhals 3 did not go as planned. A measurement at 97% power established that the limit for the radial peaking factor FH, which is a measure of the radial power distribution in the core, had been exceeded by a small amount. The simulations performed beforehand had predicted that all safety related parameters would stay within their limits during startup towards full power, which meant there were discrepancies between predictions and the real measurements. The purpose of this report is to understand the reasons for the deviations between measured and calculated values, and try to minimise them. The tools used are modern codes for cross-section generation (CASMO 4/5) along with a core simulator (SIMULATE 3/5) provided by Studsvik Scandpower. The conclusion is that the error can be split into two parts. A large part is an asymmetric tilt that is likely caused by fuel bowing. The second part is a symmetric deviation that can be reduced by changing the neutron library and accounting for errors in the measurement of thermal power. The recommendations are to load fresh fuel evenly distributed in the core to avoid large deviations in future cycles. Further study is also advised to better predict the effect of fuel bowing and to find more causes of the symmetric error.
Keywords: Fysik; Energi; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Physical Sciences; Energy; Sustainable Development; Innovation & Entrepreneurship